-4x(x+4)+7=-9

Simple and best practice solution for -4x(x+4)+7=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x(x+4)+7=-9 equation:



-4x(x+4)+7=-9
We move all terms to the left:
-4x(x+4)+7-(-9)=0
We add all the numbers together, and all the variables
-4x(x+4)+16=0
We multiply parentheses
-4x^2-16x+16=0
a = -4; b = -16; c = +16;
Δ = b2-4ac
Δ = -162-4·(-4)·16
Δ = 512
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{512}=\sqrt{256*2}=\sqrt{256}*\sqrt{2}=16\sqrt{2}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-16)-16\sqrt{2}}{2*-4}=\frac{16-16\sqrt{2}}{-8} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-16)+16\sqrt{2}}{2*-4}=\frac{16+16\sqrt{2}}{-8} $

See similar equations:

| 6/5=1/2-(x+6/5) | | 27x-1=180 | | m/5-8=-2 | | -46.5x=9.3 | | 24x+4=2x-4 | | 27x-1=26+2 | | 2t+7=-14 | | y-7=35 | | 10(z+2)-3(z-4)=3(z-2)+3(z-2) | | 39=p•78 | | 3.141/7=a/4 | | 5w+8−12w=16−15w | | 4x+x+7=4x-10 | | 2x+3x-5=-5 | | 48+3w=11w | | 2x*2+(x+10)+75=360 | | 34=-2(23-y)+4(y-4) | | 56=7/4=v | | -8x+44=20 | | -4a-25=4(1-4a)+7 | | 6(x+1)=11x-9 | | 22-w/4=-7 | | -9+5r=4r-3-6 | | 7y−4=52 | | -2=-5+.25x | | 2h+12=-4(6h-6)+2h | | 4x+3=5x-6/2 | | 2j+11=21 | | -100-52x=4x= | | 6y-18=36y= | | 6(v-80)=66 | | 24+2x=28x= |

Equations solver categories